Efficient technique for intracavity loss optimization in a dual-wavelength erbium-doped fiber laser - Al-Alimi, A.W.; Al-Mansoori, M.H.; Abas, A.F.; Mahdi, M.A.; Ajiya, M.; Adikan, Faisal Rafiq Mahamd (IOP Publishing, 2010)
An efficient technique to improve the quality of a tunable dual-wavelength fiber laser is reported. The power of both channels can be equalized with efficient intracavity loss optimization. The maximum power difference between the two wavelengths is less than +/- 0.37 dB and the output power is approximately flat within C-band.